Early Childhood Education Teachers’ and Prospective Teachers’ Understanding about Geometric Shapes - Pasiningsih, Pasiningsih (PIAUD Universitas Islam Negeri Sunan Kudus, 2022)
Children explore shapes in their daily lives. Understanding geometry is needed in children’s daily life and help them to develop their ability in solving problem. However, in Indonesia, learning math in the context of early childhood education merely focuses on learning numbers. Therefore, it is possible that teachers do not have sufficient knowledge in teaching geometry. For this reason, it is important to find out early childhood education teachers’ and prospective teachers’ understanding about geometric shapes. This study used descriptive qualitative approach to answer the research question of how early childhood education teachers and prospective teachers understand geometric shapes. The data were collected using semi-structured interviews then analysed using thematic analysis. Findings showed that early childhood education teachers and prospective teachers have lack of understanding about geometric shapes particularly in their content knowledge of 2-dimensional geometry, how to teach and assess children’s learning in geometry. It is suggested that early childhood education teachers as well as prospective teachers improve their knowledge about geometry. Early childhood education schools and universities are also expected to provide professional development and explore further other areas of mathematics, such as geometry not just focusing on numbers.